(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the importance of the method of environmental projects in the formation of environmental awareness and nature protection culture in primary school students, the process of their organization, and effective experiences. The results of the study show that project activities play a high role in developing students' environmental thinking, responsibility, and creative thinking.